Alternative specifications of the German term structure and its information content regarding inflation - Sebastian T. Schich (Deutsche Bundesbank, 1996)
The purpose of the present paper is twofold. First, it describes zero-coupon yield curve estimates for Germany from September 1972 to February 1996 using a variety of curve-fitting procedures. Second, these estimates are tested for their information content regarding future inflation.
Keywords: 330; Zinsstruktur; Schätzung; Inflation; Informationswert; Prognoseverfahren; Deutschland